海洋硅藻和绿潮藻光合特性对海洋酸化以及其他环境因子的响应 - 徐军田 (2013)
无中文摘要 While increasing atmospheric CO2 concentration and associated ocean acidification have been predicted to stimulate marine primary production, little is known about the interplay between ocean acidification and other climate change parameters, such as shoaling of upper mixing layer (UML), associated with global warming. Here, we showed that the high CO2-grown cells showed higher growth rates at the. 学位：博士后 院系专业：海洋与环境学院环境科学与工程系_环境科学 学号：2010170044